2006
DOI: 10.1016/j.virol.2005.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus nonstructural protein 2 specifically inhibits type I interferon signal transduction

Abstract: Human respiratory syncytial virus (RSV) inhibits type I interferon-induced gene expression by decreasing expression of signal transducer and activator of transcription (Stat)2. To identify the RSV protein that mediates effects on Stat2, airway epithelial cells were infected with vaccinia virus vectors that express single RSV proteins. Expression of RSV nonstructural (NS)2 protein alone was sufficient to decrease Stat2 levels. Furthermore, decreasing RSV NS2 levels using RNA interference in respiratory epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
147
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(155 citation statements)
references
References 53 publications
5
147
1
2
Order By: Relevance
“…3). In addition, the HRSV NS proteins inhibit IFNα/β signalling by inducing a decrease in Stat2 expression [87,106] (Fig. 3).…”
Section: The Role Of the Ns Proteins In The Pathogenesis Of Brsvmentioning
confidence: 99%
“…3). In addition, the HRSV NS proteins inhibit IFNα/β signalling by inducing a decrease in Stat2 expression [87,106] (Fig. 3).…”
Section: The Role Of the Ns Proteins In The Pathogenesis Of Brsvmentioning
confidence: 99%
“…We and others [16][17][18][19][20][21][22][23][24][25][26][27][28][29] have recently shown that NS1 and NS2 inhibit and/or degrade a number of proteins of the IFN induction and response pathways. We have since screened other members of these pathways, confirmed and extended the repertoire of NS targets to include: RIG-I, TRAF3, IKKε, IRF3, IRF7 and STAT2 ( Figure 1A).…”
Section: An Expanding List Of Cellular Innate Immune Proteins Targetementioning
confidence: 99%
“…With the sole exception of pneumoviruses, members of this family produce IFN-suppressor proteins such as V, W and C through co-transcriptional RNA editing of the viral P gene [10,[13][14][15]. Pneumoviruses, represented by RSV, do not use RNA editing; instead, they uniquely encode two nonstructural (NS) proteins, NS1 and NS2, which strongly suppress both IFN induction and IFNresponse pathways by inhibiting or degrading a number of signaling proteins involved in these two pathways [16][17][18][19][20][21][22][23][24][25][26][27][28][29], and thus act as essential virulence factors [30][31][32]. In pursuing the mechanism by which the NS proteins target such a diverse array of immune proteins that share little or no sequence identity, we wondered whether there is a common location of NS proteins and their targets.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous Paramyxovirus family members inhibit IFN signaling in epithelial cells through inhibition of STAT phosphorylation (26), proteasomal degradation of STAT proteins (27)(28)(29)(30), sequestration of STAT proteins in high-molecular weight complexes (31,32), and inhibition of nuclear localization of STAT proteins (33). Specifically, RSV inhibits type I IFN signaling in the respiratory epithelium through the proteasomal degradation of STAT2, a mechanism that is dependent on the expression of the RSV NS2 protein (27,34). Although it is clear that RSV inhibits IFN signaling in the epithelium, it is currently unclear whether and by what mechanisms RSV inhibits the macrophage type I IFN and type II IFN response.…”
Section: Abstract: Macrophages; Ifn; Signal Transduction; Transcriptimentioning
confidence: 99%
“…Although the capacity of RSV-encoded mechanisms to inhibit IFN-mediated signaling in epithelial cells is well documented (27,30,34,37), the ability of RSV to infect macrophages and modulate their response to IFN-a/b or IFN-g signaling has not been extensively investigated. To initially test the ability of RSV to subvert IFN-mediated responses, IFN-b-responsive pISREluciferase and IFN-g-responsive pGAS-luciferase reporter assays were used to assess transactivation of ISRE-and GAS-modulated gene products.…”
Section: Rsv Inhibits Type I Ifn-and Type Ii Ifn-inducible Transcriptmentioning
confidence: 99%